A Review of Iris Recognition Algorithms - Abdulrahman Aminu Ghali; Sapiee Jamel; Kamaruddin Malik Mohamad; Nasir Abubakar Yakub; Mustafa Mat Deris (JOIV : International Journal on Informatics Visualization, 2017)
With the prominent needs for security and reliable mode of identification in biometric system. Iris recognition has become reliable method for personal identification nowadays. The system has been used for years in many commercial and government applications that allow access control in places such as office, laboratory, armoury, automated teller machines (ATMs), and border control in airport. The aim of the paper is to review iris recognition algorithms. Iris recognition system consists of four main stages which are segmentation, normalization, feature extraction and matching. Based on the findings, the Hough transform, rubber sheet model, wavelet, Gabor filter, and hamming distance are the most common used algorithms in iris recognition stages.  This shows that, the algorithms have the potential and capability to enhanced iris recognition system.